Pengenalan Permainan Bulutangkis pada Usia Sekolah Dasar - Komari, Amat (Jurnal Pendidikan Jasmani Indonesia, 2015)
Badminton game socialization is very needed on elementary school age children because it is suitable with condition of elementary school age children posture. One of those adjustments is a tool of game used is relatively light in accordance with muscular capacity of elementary school children. To improve children’s independency in order that is expected, it needs to give an interesting extrinsic motivation to do badminton activity. In presenting game material, it is better to adjust with skill of students so that it still needs to add movements enrichment (multi lateral skill) that function to complete movement memories in their brain screen. If this movement memory is taken out at any time, it is useful for children to ease learning new movements and to do added movement in rescuing themselves from possibility injured. In order that children do not bored fastly, presentation method uses playing approach. Therefore in foreplay it is chosen playing activity that can increase temperature of body to prepare physical and psychological condition before running heavier activities. Types of introduction through games lead to badminton activity are, for example, by shot ball, and head throwing by shuttlecock. Although badminton has been competed on early age, the important thing through this game competition is students can add experiences to recognize their environment more, look playing-schedule, prepare eat and drink time, prepare clothes, shoes and choose transportation means in order not coming late. Besides that, they can learn accepting defeat, conceding strength of other people and gaining social-interaction experiences not given at school. The material presented consists of many varieties of foreplay, running variation, individual gymnastics, in pair gymnastics, games, kinds of raket-handling, overhead stroke posture, lob, dropshot and smash stroke also foot-movement doing. Keywords: Badminton, Early Age, Socialization